QuEChERS: a new sample preparation approach for the determination of ibuprofen and its metabolites in soils - Bragança, Idalina (2012)
Ibuprofen is one of the most used active pharmaceutical ingredients worldwide. A new method for the analysis of ibuprofen and its metabolites, hydroxyibuprofen and carboxyibuprofen, in soils is presented. The extraction of these compounds from the soil matrices was performed by using a modified quick, easy, cheap, effective, rugged, and safe (QuEChERS) method. The method involves a single extraction of the investigated compounds with purified water (acidified at pH 2.5 with hydrochloric acid), and a slow and continuous addition of the QuEChERS content, followed by the addition of acidified acetonitrile (1% acetic acid), prior to the determination by liquid chromatography coupled with fluorescence detection (LC–FLD). Validation studies were carried out using soil samples with a range of organic carbon contents. Recoveries of the fortified samples ranged from 79.5% to 101%. Relative standard deviations for all matrix–compound combinations did not exceed 3%. The method quantification limits were ≤22.4 μg kg−1 in all cases. The developed method was applied to the analysis of sixteen real samples.